Spatial Intelligence and Geographic Skills: REACT Model on Regional Development and Growth Materials - Risky Andias Oktavian; Dwiyono Hari Utomo; Alfyananda Kurnia Putra; Yuswanti Ariani Wirahayu; Syah Rizal (Abjadia, 2023)
The REACT model is constructive contextual learning that emphasizes the meaning of learning and the knowledge built in students' minds. This study aims to determine the effect of the REACT model on students' Spatial Intelligence and Geographic Skills. This research uses Quasy Experimental with Posttest Only Control Group Design. The subjects used in the study were students of class XII Social Sciences 2 as an experimental class and XII Social Sciences 3 as a control class at Senior High School 10 Malang in the academic year 2022/2023. Determination of the sample using purposive sampling technique with the consideration of having a middle school final exam score that is almost the same. The research instrument uses an essay test referring to geographic skills and spatial intelligence indicators. Data analysis used the Independent-Sample T Test and the Mann-Whitney U Test with a significance level of 0.05. The significance value of the Independent-Sample T-Test for spatial intelligence shows an effect of the REACT learning model on students' spatial intelligence with a value of 0.004 0.05, with the spatial concept indicator having the highest influence. In contrast, the reasoning process indicator has the most effect low. The significance value of the Mann-Whitney U test geographical skill test shows an impact of the REACT learning model on students' spatial intelligence with a value of 0.004 0.05, with the indicator answering geographical questions having the highest impact, while the indicator asking geographic questions has the highest influence the lowest.